The Power of E-Book as the Media for Self-directed Learning in the Teaching of Basic English - Annajah Annajah; Chindy Hanggara Rosa Indah; Suhartatik Suhartatik (Journey: Journal of English Language and Pedagogy, 2025)
Evolution technology has influenced the development of utilization instructional media in all level education. E-book as the product of digital transformation play a major role in supporting self-directed learning. The power of E-book in terms of accessibility, efficiency and multi media integration can be able to enforce students’ motivation and independence. This study aim to design E-Book as the media for Selfdirected Learning in the Teaching of Basic English. Research and Development is provided to know the feasibility of the product validated by the experts of media and learning materials. The outcome reveals that the material expert validation scored 94%, indicating suitability for use, while the media expert validation scored 77.8%, demonstrating the product’s feasibility after revisions.The aspect of accessibility and flexibility, E-Book is considered as feasible media to be used for independence learning.